Editorial Vol. 11, Nº 3 - dos Santos, Rodrigo Pereira; Freire, Andre Pimenta (iSys - Journal of Information Systems, 2018)
Edition Number 3 of Volume 11 (2018) presents 5 (five) original papers submitted directly to the journal.